2009
DOI: 10.1055/s-0028-1128142
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of Insulin Sensitivity by a Novel Drug, BGP-15, in Insulin-resistant Patients: A Proof of Concept Randomized Double-blind Clinical Trial

Abstract: The efficacy and safety of the new drug, BGP-15, were compared with placebo in insulin-resistant patients in a 28-day dose-ranging study. Forty-seven nondiabetic patients with impaired glucose tolerance were randomly assigned to 4 weeks of treatment with 200 or 400 mg of BGP-15 or placebo. Insulin resistance was determined by hyperinsulinemic euglycemic clamp technique and homeostasis model assessment method, and beta-cell function was measured by intravenous glucose tolerance test. Each BGP-15 dose significan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
83
0
3

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(89 citation statements)
references
References 31 publications
2
83
0
3
Order By: Relevance
“…BGP-15 represented an attractive drug to investigate in a setting of HF and AF because it was previously shown to coinduce HSP70 in skeletal muscle 31,32 , and reduced cardiac HSP70 levels were associated with AF in patients 15,16 . Furthermore, BGP-15 had been shown to be safe in humans [9][10][11] , and clinical phase II/b testing for type 2 diabetes has been completed 42 . Interestingly, BGP-15 did not co-induce HSP70 in cardiac muscle of the HF þ AF model or the MURC model.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…BGP-15 represented an attractive drug to investigate in a setting of HF and AF because it was previously shown to coinduce HSP70 in skeletal muscle 31,32 , and reduced cardiac HSP70 levels were associated with AF in patients 15,16 . Furthermore, BGP-15 had been shown to be safe in humans [9][10][11] , and clinical phase II/b testing for type 2 diabetes has been completed 42 . Interestingly, BGP-15 did not co-induce HSP70 in cardiac muscle of the HF þ AF model or the MURC model.…”
Section: Discussionmentioning
confidence: 99%
“…BGP-15 is administered orally and has been shown to have an excellent safety profile in multiple human clinical trials in healthy individuals 9,10 and insulin-resistant nondiabetic patients 11 . The initial rationale for assessing the therapeutic potential of BGP-15 in an animal model with a failing heart and increased susceptibility to AF was related to its role as a co-inducer of the stress inducible form of heat-shock protein 70 (HSP70/72) 12 .…”
mentioning
confidence: 99%
“…*P Ͻ 0.05, **P Ͻ 0.01 assessed by t-test. impaired glucose tolerance (30). BGP-15 is thought to activate HSP72 via modification of membrane microdomain-associated stress-sensing and -signaling mechanisms (50,52) and by prolonging the binding of HSF1 to heat shock response element (27).…”
Section: Discussionmentioning
confidence: 99%
“…Finally, a recent study demonstrated that besides heat shock either overexpression or pharmacologic induction of Hsp70 by a novel chaperone co-inducer BGP-15 was sufficient to prevent the development of obesity-induced insulin resistance in fat-fed mice [43]. Strikingly, a 1-month treatment with BGP-15 significantly improved insulin sensitivity in insulin-resistant, nondiabetic human patients [44]. These protective effects may be related to an improved protein homeostasis, a more efficient modulation of signaling networks and to a better connectivity of subcellular organellar networks, such as the ER and the cytosol [8,45].…”
Section: Obesity and Diabetes As A Metabolic Distress: The Protectivementioning
confidence: 99%